The Influence of Halal Awareness and Online Customer Reviews on Purchase Decisions of Luxcrime Cosmetics through TikTok Shop; Moderated by Religiosity (A Study on Muslim Female Students of Politeknik Negeri Medan) - Farah Dhiba; Rizal Agus; Ahmad Kholil; Muhammad Zuhirsyan; Anriza Witi Nasution; Ermyna Seri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to determine the influence of halal awareness and online customer reviews on the purchase decisions of Luxcrime cosmetics through TikTok Shop, as well as the moderating effect of religiosity on the relationship between halal awareness and online customer reviews toward purchase decisions. The dependent variable in this study is purchase decision, while the independent variables consist of halal awareness and online customer reviews, with religiosity serving as the moderating variable. The research sample consisted of 94 respondents, all of whom were Muslim female students from Politeknik Negeri Medan. Primary data were collected through questionnaires, while secondary data were obtained from company publications. The questionnaire instrument was tested for validity and reliability using a Likert scale. Data analysis was conducted using multiple regression, t-test (partial), F-test (simultaneous), and the coefficient of determination at a 5% significance level, employing SPSS version 26